Identifikasi Dan Uji Virulensi Penyakit Antraknosa Pada Pascapanen Buah Cabai - Ramdan, Evan Purnama; Arti, Inti Mulyo; Risnawati, Risnawati (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
Postharvest handling is a crucial factor for maintaining food loss caused by decreasing postharvest products. Anthracnose is an important disease in postharvest chili, so this study aims to identify and test the level of virulence from anthracnose in postharvest chili. The chili fruit samples in this study were taken from Pal Depok market which were then isolated to obtain pathogenic fungi isolates. The pathogens that were successfully isolated were then purified to be morphologically characterized from both morphology and conidia. After the pathogen has been identified then the level of virulence of the pathogen is calculated by calculating the lesions that arise due to pathogenic infections in apples. The results of the identification showed that the causes of anthracnose in chili fruit were C. acutatum and C. gloeosporioides. Although, the two fungi had a low virulence level, C. gloeosporioides had the ability to cause larger lesions (0.9333 cm) compared to C. acutatum (0.8667 cm).